IMPLEMENTATION OF THE ENVIRONMENTAL CARE AND CULTURE MOVEMENT IN SCHOOLS - Khamid, Muh; Raharja, Setya; Ramadhan, Aqsal Rizky; Apriyanto, Ridwan Eko; Salam, Khatibul Umam (Universitas Labuhanbatu, 2025)
Purpose–This research aims to describe the implementation of the Environmental Care and Culture Movement in Schools at the National Adiwiyata SchoolMethodology–The research uses a qualitative approach in the type of case study at SMA Negeri 2 Wates. Data sources include school principals, vice principals for curriculum, heads of adiwiyata, teachers, adiwiyata cadres, school committees, curriculum documents, and other related documents. Data were collected through in-depth interviews, observations, and document studies. Data analysis uses an interactive model.Findings–The implementation is carried out with various concrete actions that integrate aspects of Environmentally Friendly Behavior, namely cleanliness, sanitation and drainage functions, waste management, planting and maintenance of trees/plants, water conservation, energy conservation, and innovations related to Environmentally Friendly Behavior into learning in all subjects, extracurricular activities, and self-habituation of school residents. Environmentally Friendly Behavior is applied to the surrounding community through community-based programs. The SchoolSchool establishes a working network with external parties to support the movement's sustainability. Campaigns and publications are carried out through concrete actions to increase environmental awareness. Schools form and empower adiwiyata cadres as agents of change that can encourage and mobilize school residents to implement environmentally friendly behaviors and the formation of adiwiyata ambassadors.Significance—Schools can consider the study's results to effectively manage and implement the Environmental Care and Culture Movement in Schools in the National Adiwiyata. Keywords : Implementation, Environmental care, Culture movement schools